Cultural transitions and dialogues in the Great Silk road area: experience in preventing cultural deviations (Journal of Philosophy Culture and Political Science, 2021)
History shows that the Great Silk Road and the Islamic Renaissance were the factors that influenced the civilizational turn from cultural anomalies in the nomads of Central Asia.  If settled cultures occupied the space and divided it, the nomads themselves were divided in space. The deviant division between nomadism and stable agricultural cultures began to be resolved through cultural dialogue in the phenomenon of the Great Silk Road.  The purpose of the article is to analyze the experience of the Great Silk Road in solving deviant anomalies between settled (dihanic-irrigation) and nomadic cultures formed in Central Asia.    This gave the Turkic peoples the opportunity to exchange great cultures and innovations at the global level. Scientists such as Avicenna, Biruni, Firdousi, Khayyam, Khorezmi, Rudaki, Rashid-ad-Din, Ulugbek, Saadi, Al-Farabi and Balasagun were born on the caravan roads, which opened the doors of great achievements for humanity. Along the Great Silk Road through Central Asia, the works of Aristotle, Plato and Hippocrates, which remained under the European medieval restrictions, «survived» and developed. The geopolitical role of Central Asia in the history of mankind is great, it served as a link between the differences and cultural deviation between the Roman and steppe, Turkic and Iranian, Arab and Chinese empires from antiquity to the Middle Ages. According to Arnold Toynbee, in the area of the Great Silk Road, "it is not difficult to see that this place, where the giant Turkic empire flourished and lived, was the center of future civilizations or one civilization."  In Central Asia, a cultural renaissance flourished in the area of the Great Silk Road, and the basis for future modern knowledge was formed.Key words: The Great Silk Road, cultural dialogue, cultural deviation, nomadism, settlement, civilization, cultural transitions.